An Analysis of Video for Speaking Learning Material based on Learning Principles of Speaking Skill - Putri Nugra Fitria; Delvi Wahyuni (Universitas Negeri Padang, 2023)
The rapid development of technology has contributed to the development in the world of education, especially in learning media. Currently, there are many YouTube creators who create educational content, including the application of German conversation in daily life. However, the video channel cannot be considered as a good and appropriate learning medium if the videos do not meet the rules of speaking learning and must comply with the criteria for a good teaching medium. Therefore, before using the medium, it must be ensured that the medium is suitable for use according to the criteria. The purpose of the research is to analyze the suitability of “Asking for Opinion Video produced by Ruangguru” with the teaching principles of speaking skills. This research employed a quantitative descriptive design that concerns with analysis of learning materials In teaching principles; this video fulfils two out of three principles. The video provides something for learners to talk about and manipulates physical arrangements to promote speaking practice. Meanwhile, the video does not create opportunities for students to interact by using group work or pair work. In addition, based on the video analysis, the video fulfils five out of five which means all of the principles. The video is relevant to the substance of the material. The video is compatible with the curriculum and basic competency. The video is attractive. The duration of the video is appropriate. Lastly, the video is valid and original to be used.